THE EFFECTIVENESS OF USING GAME-BASED TECHNOLOGIES IN ENGLISH LESSONS IN PRESCHOOL EDUCATION - Choriyeva Xurmo (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This article explores the effectiveness of using game-based technologies in English lessons for preschool children. The study highlights how interactive and play-based approaches contribute to the development of vocabulary, listening, speaking, and communication skills in young learners. Emphasis is placed on the integration of educational games, digital applications, and collaborative activities to enhance engagement, motivation, and practical language use. The findings provide practical recommendations for preschool educators to implement game-based technologies effectively, ensuring developmentally appropriate and stimulating English lessons.